EasySSR: a user-friendly web application with full command-line features for large-scale batch microsatellite mining and samples comparison - Alves, Sandy Ingrid Aguiar; Ferreira, Victor Benedito Costa; Dantas, Carlos Willian Dias; Silva, Artur Luiz da Costa da; Ramos, Rommel Thiago Jucá (Frontiers in Genetics, 2023)
Microsatellites, also known as SSRs or STRs, are polymorphic DNA regions with tandem repetitions of a nucleotide motif of size 1-6 base pairs with a broad range of applications in many fields, such as comparative genomics, molecular biology and forensics. However, the majority of researchers do not have computational training and struggle while running command -line tools or very limited web tools for their SSR research, spending a considerable amount of time learning how to execute the software and doing the post-processing data tabulation in other tools or manually, time that could be used directly in data analysis. We present EasySSR, a user-friendly web tool with command-line full functionality, designed for practical use in batch identifying and comparing SSRs in sequences, draft or complete genomes, without previous bioinformatic skills to run. EasySSR requires only a FASTA and an optional GENBANK file of one or more genomes to identify and compare STRs. The tool can automatically analyze and compare SSR in whole genomes, convert GenBank to PTT files, identify perfect and imperfect SSRs, coding and non-coding regions, compare their frequencies, abundancy, motifs, flanking sequences, and iterations, producing many outputs ready for download such as PTT files, interactive charts and excel tables, giving the user the data ready for further analysis in minutes. EasySSR was implemented as a web application, which can be executed f rom any browser and is available for free at https://computationalbiology.ufpa.br/easyssr/ . Tutorials, usage note and download links to the source code can be found at https://github.com/engbiopct/EasySSR .